Pituitary deficiency and precocious puberty after childhood severe traumatic brain injury: a long-term follow-up prospective study. Issue 5 (May 2019) - Dassa, Yamina; Crosnier, Hélène; Chevignard, Mathilde; Viaud, Magali; Personnier, Claire; Flechtner, Isabelle; Meyer, Philippe; Puget, Stéphanie; Boddaert, Nathalie; Breton, Sylvain; Polak, Michel
Abstract : Objectives: Childhood traumatic brain injury (TBI) is a public health issue. Our objectives were to determine the prevalence of permanent pituitary hormone deficiency and to detect the emergence of other pituitary dysfunctions or central precocious puberty several years after severe TBI. Design: Follow-up at least 5 years post severe TBI of a prospective longitudinal study. Patients: Overall, 66/87 children, who had endocrine evaluation 1 year post severe TBI, were included (24 with pituitary dysfunction 1 year post TBI). Main outcome measures: In all children, the pituitary hormones basal levels were assessed at least 5 years post TBI. Growth hormone (GH) stimulation tests were performed 3–4 years post TBI in children with GH deficiency (GHD) 1 year post TBI and in all children with low height velocity (<−1 DS) or low IGF-1 (<−2 DS). Central precocious puberty (CPP) was confirmed by GnRH stimulation test. Results: Overall, 61/66 children were followed up 7 (5–10) years post TBI (median; (range)); 17/61 children had GHD 1 year post TBI, and GHD was confirmed in 5/17 patients. For one boy, with normal pituitary function 1 year post TBI, GHD was diagnosed 6.5 years post TBI. 4/61 patients developed CPP, 5.7 (2.4–6.1) years post-TBI. Having a pituitary dysfunction 1 year post TBI was significantly associated with pituitary dysfunction or CPP more than 5 years post TBI. Conclusion: Severe TBI in childhood can lead to permanent pituitary dysfunction; GHD and CPP may appear after many years. We recommend systematic hormonal assessment in children 1 year after severe TBI and a prolonged monitoring of growth and pubertal maturation. Recommendations should be elaborated for the families and treating physicians.